2022
DOI: 10.1021/acsami.1c22280
|View full text |Cite
|
Sign up to set email alerts
|

A Mucin-Deficient Ocular Surface Mimetic Platform for Interrogating Drug Effects on Biolubrication, Antiadhesion Properties, and Barrier Functionality

Abstract: Dry eye disease (DED) affects more than 100 million people worldwide, causing significant patient discomfort and imposing a multi-billion-dollar burden on global health care systems. In DED patients, the natural biolubrication process that facilitates pain-free blinking goes awry due to an imbalance of lipids, aqueous medium, and mucins in the tear film, resulting in ocular surface damage. Identifying strategies to reduce adhesion and shear stresses between the ocular surface and the conjunctival cells lining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Both cell lines express mucins at their apical surfaces, albeit with different expression levels and distributions. [ 12,15 ] To establish the corneal/conjunctival epithelial interfaces, HCjE cells were cultured on circular collagen‐coated glass coverslips glued on custom‐designed frames (referred to as top plates, TP, Experimental Section), and hTCEpi cells were cultured on collagen‐coated glass‐bottom culture dishes (referred to as bottom plates, BP, Experimental Section). To measure the distance between cell layers, diffraction‐limited fluorescent beads were adsorbed to the glass surfaces via van der Waals forces prior to cell seeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both cell lines express mucins at their apical surfaces, albeit with different expression levels and distributions. [ 12,15 ] To establish the corneal/conjunctival epithelial interfaces, HCjE cells were cultured on circular collagen‐coated glass coverslips glued on custom‐designed frames (referred to as top plates, TP, Experimental Section), and hTCEpi cells were cultured on collagen‐coated glass‐bottom culture dishes (referred to as bottom plates, BP, Experimental Section). To measure the distance between cell layers, diffraction‐limited fluorescent beads were adsorbed to the glass surfaces via van der Waals forces prior to cell seeding.…”
Section: Resultsmentioning
confidence: 99%
“…The gap distance was determined via laser scanning microscopy. Upon reaching confluency (>70%), these cell types can be differentiated into stratified epithelia expressing membrane‐tethered mucins (Figure S1, Supporting Information, [ 12,14,16 ] and Figure 1A). High calcium and serum content in the culture medium induces the stratification process, which is marked by the expression of membrane‐associated mucins on the epithelia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that rh -lubricin is able to adsorb onto and form a viscous, hydrated layer on hydrophilic glass surfaces, 11 as is the case during our heating step. Other in vitro models incorporating corneal and conjunctival epithelial cells also show that both topical treatment using native human lubricin (Seo et al, 2019) 23 and the incubation of cells in solution with rh -lubricin 21 resulted in the adherence of lubricin to the epithelial surface. We demonstrated that adsorbed rh- lubricin alone was not sufficient to maintain a fully wetted area when rh- lubricin was absent from the model tear film.…”
Section: Discussionmentioning
confidence: 95%